Consumer Purchasing Behavior Toward Green Environment in the Healthcare Industry: Mediating Role of Entrepreneurial Innovation and Moderating Effect of Absorptive Capacity - Sarfraz, Muddassar; Raza, Mohsin; Khalid, Rimsha; Liu, Tong; Li, Zeyu; Niyomdecha, Lubna (Frontiers in Public Health, 2022)
Entrepreneurial innovations lead to transformations in the existing business model, involving them integrating the new knowledge into the established entrepreneurial activities. The current study combines marketing strategies, entrepreneurial innovation, absorptive capacity, and consumer purchasing behaviour in the health sector. This study investigates the impact of packaging and labelling strategies on entrepreneurial innovation and consumer purchasing behaviour. Therefore, this study also investigates the mediating effect of entrepreneurial innovation between packaging and labelling strategies and consumer purchasing behaviour. The study examines the moderating role of absorptive capacity between entrepreneurial innovation and consumer purchasing behaviour. While using convenience sampling, this study used the consumer of medications as a sample from China. The research adopted a quantitative method to conduct the study analysis. A well-structured questionnaire with a 5-point Likert scale has used for the study analysis. The adopted questionnaires were utilized in data collection with 702 with a 70% response rate, and Smart PLS was used to analyze the data. The findings of this study indicate that packaging and labelling strategies significantly influence entrepreneurial innovation and consumer purchasing behaviour. Entrepreneurial innovation significantly mediates the packaging and labelling strategies and consumer purchasing behaviour. The moderating role of absorptive capacity significantly affects entrepreneurial innovation and consumer purchasing behaviour. The implications of the investigated model with innovative marketing strategies give new insights for managerial, policymakers, and research perspectives.